Ireland : Financial Sector Assessment Program-Technical Note on Financial Interconnectedness of the Market-Based Finance Sector. (IMF Staff Country Reports; Country Report ;, 2022)
This technical note1 investigates the interconnectedness between the market-based finance (MBF) sector in Ireland and the rest of the financial system, with a view to assessing potential financial stability risks. The MBF sector, the largest component of the financial system, totals over 14 times GDP and is comprised of the funds sector-both money-market (170 percent of GDP) and investment funds (850 percent of GDP)- as well as other financial institutions (OFIs), which comprise of special purpose entities (SPEs, 240 percent of GDP) and a catch-all category entitled "OFI residual" (160 percent of GDP). Chapter I provides an overview of the potential financial stability risks associated with the MBF sector, with a focus on the funds sector, and places it in its domestic and global context. Chapter II maps out the interlinkages between the non-banks, banks, and the real sector using network analysis to assess the strength and direction of interconnectedness. Chapter III delves into the balance sheet exposures of major categories of Irish funds, the largest component of the MBF sector, to further assess channels of risk transmission. The analysis focuses on a network of complex inter-sectoral financial relationships, based on a range of lending and borrowing instruments, and several findings emerge.